Новые виды паразитических перепончатокрылых рода Ormyrus (Hymenoptera, Ormyridae) из аридных районов Палеарктики - Зерова, М.Д. (Вестник зоологии, 1985)
Six Ormyrid hymenopteran species are described as new: Ormyrus bucharicus sp. n. (type-locality: Bukhara distr., Southern slopes of Kuldzhuktau Mts.) similar to 0. gratiosus Förster, differs from it by two antenna! rings in both sexes and smooth abdomen sculpture; O. lanatus sp. n. (type-locality: Kazakhstan, Tshingildy) — by antennal structure similar to O. halimodendri sp. n. and O. parvulus sp. n., differs by relatively elongated abdomen; O. halimodendri sp. n. (type-locality: Turkmenia, Repetek) and O. parvulus sp. n. (type-locality: shore of Elton lake) - two closely related species differing by abdominal sculpture: coarser and denser in O. parvulus. O. laccatus sp. n. (type-locality: Turkmania, Karabekaul distr.) - similar to O. similis sp. n. differs by antennal structure with two rings and flagellar segments broadened toward apex. Type-material is deposited in the Institute of Zoology, Ukrainian SSR Academy of Sciences (Kiev). A key to all Palearctic Ormyrus species is given.